Deprivation Influence on the Teenager Personality Formation and Socialization - Podolets, O. O. (Psychological Prospects Journal, 2012)
Deprivation influence on the teenager personality formation is observed in the article. The features of teenagers’ socialization who have been subjects to influence of various kinds deprivation were considered.